Sheep fattening: A manual for livestock farmers and extension workers in the Ethiopia - Wamatu, Jane; Zeleke, Muluken; Abiso, Tesfaye (International Center for Agricultural Research in the Dry Areas, 2021)
Sheep fattening has been a long-standing practice in Ethiopia, which is particularly geared towards meeting the demand, which typically increases during festive seasons. It is considered low-risk and more profitable than rearing large ruminants. The traditional sheep fattening cycle can last six months or longer. Farmers attribute the long fattening period to a lack of adequate and high-quality feed, poor management due to a lack of skills and knowledge of improved fattening practices and supplementary feeding methods. Thus, improving the feeds and nutrition aspects of the small ruminant value chains became one of the core intervention areas for the International Center for Agricultural Research in Dry areas, ICARDA. Focus has been put on market-oriented sheep fattening that entails short-term intensive feeding of rams prior to sale using formulations from locally available feed sources. This manual provides simple and tested practical guidelines for sheep fattener and extension workers in Ethiopia. It contains information on feeds and feeding management options that can be applied by small-scale producers.